CRIME TAX AND FINANCIAL FRAUD AS A THREAT TO PUBLIC FINANCES IN POLAND - Jacek BINDA; Ryszard Bełdzikowski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The paper attempts to identify the scale of fiscal crime perpetrated in Poland in terms of two tax liabilities: the value of goods and services (VAT) and excise duties. The size of quota’s fraud, especially in case of VAT is already so large that it starts to undercut the tax revenue of the state budget. This crime, is not the only reason for the reduction of planned incomes from tax on the value of goods and services to the state budget in the last 3 years. However, it is a very destructive factor influencing the behavior of the economic and tax systems, especially small and medium-sized family businesses. The scale of the described problem leads to the conclusion that currently in Poland there is specialized, well-organized crime using VAT mechanisms to extort tax debt from the Inland Revenue Offices and cheating commercial contractors on the value of the unregulated 23% VAT. This situation creates serious criminal threats to social, economic and public finances.